Involvement of Heat Shock Proteins on the Transcriptional Regulation of Corticotropin-Releasing Hormone in Medaka - Uchimura, Tomoya; Hara, Seiji; Yazawa, Takashi; Kamei, Yasuhiro; Kitano, Takeshi (Frontiers in Endocrinology, 2019)
Medaka (Oryzias latipes) are teleost fish with a XX/XY sex determination system. Recently, it was reported that high temperature (HT) induced the masculinization of XX medaka by increasing the levels of cortisol, a major glucocorticoid produced by interrenal cells in teleosts. Cortisol secretion is regulated by adrenocorticotropic hormone (ACTH) secreted from the pituitary gland, which is partly regulated by corticotropin-releasing hormone (CRH) secreted from the hypothalamus. In teleosts, two crh paralogs, named crha and crhb, have been identified. Recently, the expression of crhb but not crha was upregulated by HT during gonadal sex differentiation period in medaka and loss-of-functions of its receptors under HT suppressed masculinization of XX medaka and increase of cortisol levels, suggesting that crhb is involved in masculinization induced by HT. However, the transcriptional regulation of crhb under HT has not been elucidated. We analyzed the gene expression pattern in the hypothalamus of medaka embryos incubated under HT using DNA microarray. The expressions of heat shock protein (hsp) genes, such as hsp70.1 and hsp30, were increased. Overexpression of hsp70.1 or hsp30 in cultured rat hypothalamic 4B cells significantly induced crh gene expression. Moreover, hypothalamic hsp70.1-overexpressing transgenic medaka also showed increased crhb gene expression that increased cortisol levels compared with fish incubated at a normal temperature. These results provide the first evidence that HSPs induce cortisol levels by elevating crhb gene expression in the hypothalamus.